Faktor-faktor Struktural yang Menyebabkan Timbulnya Konflik antara Etnik Melayu dengan Etnik Madura di Kabupaten Sambas Kalimantan Barat: The Stuctural Factors Causing the Conflict between the Malay and the Madurese Ethn - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 2003)
This research aims at describing a conflict process and identifying some aspects causing and supporting the Malay-Madurese etnic conflict at Sambas district. For these purpose, the primary research data from interviews and observation and the secondary data from various documents related to the conflict are qualitively analyzed with arranging, sorting, grouping, and categorizing the data. The result of the research shows that the structural factors causing and supporting the ethnic conflict could be categorized into two groups, they are economic and political factors. The economic aspects includes: 1) unfair competition in getting agricultural-economic resources, especially the land